Dynamic Response Analysis of Wedge-Shaped Rock Slopes under Harmonic Wave Action - Yihan Du; Wenzhi Xu; Wei Han; Bo Huang; Hui Liu; Xuze Du (Buildings, 2023)
In dynamic disasters involving rock slopes, wedge failures formed by complex structural discontinuities are more predominant, and the dynamic response associated with them remains a classic concern in rock slope engineering. To address this concern, this paper utilized refined modeling to analyze a wedge-shaped rock slope by inputting horizontal harmonics as loads. We conducted dynamic response analyses by varying the inclination of the structural surface on the wedge-shaped rock slope, the axial offset angle, the friction coefficient, and the configuration of the single sliding surface. The results in this paper indicate that for wedge-shaped and single-sliding-surface configurations of rock slopes, with an increase in the structural surface inclination angle, the dynamic response of the sliding body, stress distribution, excellent frequency, and spectrum values all increase. Furthermore, wedge-shaped rock slopes’ dynamic responses are more significant than those of single-sliding-surface rock slopes. For wedge-shaped rock slopes, increases in the axial offset angle and structural surface friction coefficient reduce the dynamic response, excellent frequency, and spectrum values. Meanwhile, within the context of the axial offset angle conditions in wedge-shaped rock slopes, the dynamic response, excellent frequency, and spectrum values are better than the variations in the structural surface friction coefficient. Under the influence of these factors, stress concentration occurs at the sliding fronts of rock slopes.